2-Aryl Benzimidazole Derivatives Act as Potent Urease Inhibitors; Synthesis, Bioactivity and Molecular Docking Study. (2nd January 2023) - Saeedian Moghadam, Ebrahim; Al-Sadi, Abdullah Mohammed; Talebi, Meysam; Amanlou, Massoud; Amini, Mohsen; Abdel-Jalil, Raid
Abstract: Herein, we have synthesized a series of novel fifteen 2-aryl benzimidazole derivatives 8a–o and tested their bioactivity as potent urease inhibitors. The structures of the 8a–o were elucidated using spectroscopic technics ( 1 H-NMR, 13 C-NMR, MS), elemental analysis, and melting point. The urease inhibition activity was evaluated using the urease enzyme inhibition kit. All 8a–o showed higher urease inhibition activity (7.74 to 21.18 µM) in comparison to thiourea and hydroxyurea as standard (IC50 : 22 and 100 µM respectively). 8m, 8n, and 8o exhibited the best activity with the IC50 value of 7.74, 8.09, and 8.56 µM respectively. Docking study represented the possible mode of interactions between the most active compound and the residues of the enzyme's active site. To investigate the cytotoxicity profile of the target compounds, the MTT assay was performed on two different cell lines. The results showed that all 8a–o derivatives display IC50 values higher than 50 µM toward both tested cell lines. Graphical Abstract: UF0001